The sexual violence against minors and their legal-ethical and canonical protection - STAWNIAK, HENRYK; JARZĄBEK-BIELECKA, GRAŻYNA; BIELECKA-GĄSZCZ, ANNA (Prawo Kanoniczne, 2017)
In the common good of the state and the Church there is care about the protection of children and young people. The task of these communities is initially to recognize and respect the rights of minors and the care to ensure the safe development environment, free of exploitation, violence and manipulation. The state and ecclesial communities are committed to the physical, spiritual and emotional growth of children and youth people and to the exclusion of the situation of any physical or mental violation of minors integrity. All abuses in this regard are widely condemned by both communities, and they cause righteous indignation. In the state and church legal system, acts related to violence against children and adolescents are considered serious crimes. Disturbing phenomena related to sexual harassment or child pornography have resulted in legislation that severely penalizes these crimes. The article will present crimes of sexual violence against minors in the legal-criminal, ethical and canonical systems. This comparative approach will be going to show the offenses in both systems, victims of crime and their perpetrators, the criminal sanctions and the real concern for the state and the Church for the protection of minors.